Attitudes about adult vaccines and reminder/recall in a safety net population. Issue 52 (19th December 2017) - Albright, Karen; Hurley, Laura P.; Lockhart, Steven; Gurfinkel, Dennis; Beaty, Brenda; Dickinson, L. Miriam; Libby, Anne; Kempe, Allison
Highlights: Little is known about adult patients' attitudes toward vaccination and reminder/recall. Twelve focus groups were conducted with 68 patients in a safety net health system. Participants had little knowledge of specific adult vaccines other than influenza. All participants were in favor of receiving reminder/recall notices for adult vaccines. Improved communication between providers and patients is needed to increase awareness about adult vaccines. Abstract: Little is known about adult patients' attitudes toward vaccination and preferences for reminder/recall. The objective of this study was to determine patient perspectives on adult vaccines generally; attitudes about Tdap, pneumococcal polysaccharide (PPSV-23), and seasonal influenza vaccines specifically; and preferences for adult reminder/recall delivery. Twelve focus groups were conducted with 68 patients in a safety net health system. The sample was stratified by preferred language (English or Spanish), age (18–64 or 65+), and health status (with or without chronic conditions). Participants expressed positive attitudes toward vaccines generally, but had little knowledge of specific vaccines other than influenza, about which they expressed concerns. Although none reported previous experience receiving reminder/recall notices for adult vaccines, all were in favor of receiving them. These results suggest potential patient interest in greater adoption of evidence-based methods to improve immunization rates, and highlight the need for improved communication between providers and patients about adult vaccines.